Metrocoris Mayr (Insecta: Hemiptera: Gerridae) of India with descriptions of five new species - Basu, Srimoyee; Polhemus, D. A.; Subramanian, K. A.; Saha, G. K.; Venkatesan, T. (Zootaxa, 2016)
The Metrocoris fauna of India is reviewed and five new species are described from India: M. murtiensis Basu, Polhemus and Subramanian sp. nov. belonging to the nigrofasciatus species group, M. dinendrai Basu, Polhemus and Subramanian sp. nov. and M. darjeelingensis Basu, Polhemus and Subramanian sp. nov. of the compar species group, M. deceptor Basu, Polhemus and Subramanian sp. nov. (previously treated as M. quynhi Tran & Zettel in Basu et al., 2015) of the anderseni species group, and M. lavitra Basu, Polhemus, Subramanian and Saha sp. nov., which does not fit well into any currently established species group. The new species proposed are compared to all other known species, and a key to all the species of Indian Metrocoris is provided, accompanied by a table for comparison of key morphological characters, and a map and table of distributional details.